The Linkage of Soil pH, Phosphorus Availability, and Exchangeable Aluminum in Andisol and Recommendations for Soil Improvement - Erwinda Erwinda; Rufaidah Qonita Muslim; Mira Media Pratamaningsih; Diah Puspita Hati; Pronika Kricella; Erna Suryani; Helena Lina Susilawati (Jurnal Ilmu Pertanian Indonesia, 2025)
The Indonesian government implemented a program known as the Food Estate in Humbang Hasundutan to enhance food security. This initiative involved cultivating strategic food commodities on large-scale agricultural land. The soil type in this area is classified as Andisol, which is naturally fertile. Nevertheless, the food and horticultural crop practices in Andisol scarcely consider soil health, fertility, and sustainability. This study was conducted on the Andisols of Humbang Hasundutan to determine the limiting factors of soil chemical properties to support sustainable land management. Soil samples were collected from the topsoil layer (0-30 cm) at 95 locations using a grid-based sampling system. These samples were analyzed for pH, phosphorus availability, and exchangeable aluminum. The data were examined through correlation tests, with soil improvement levels identified using K-means clustering. The results showed that the Andisols in Humbang Hasundutan had an acidic pH level (5.30), extremely high organic carbon content (8.23%), moderate total nitrogen level (0.44%), extremely low potential and available phosphorus levels (12.66 ppm and 4.15 ppm), very low base saturation (6.48%), and relatively high exchangeable aluminum (Alexch) (1.03 cmol.kg-1). Correlation analysis revealed a negative relationship between pH and P availability, while Alexch showed a positive correlation with P availability. However, P availability in Andisol was not significantly influenced by variations in Alexch or soil pH. Soil improvement recommendations were categorized into three groups: 60 locations requiring very high P fertilization, 28 locations requiring high P fertilization, and 7 locations requiring moderate P fertilization, along with the application of soil amendments, such as dolomite or guano phosphate, to reduce aluminum levels. Keywords: andisol, exchangeable-Al, P availability, soil acidity